2015
DOI: 10.11648/j.jgo.20150301.14
|View full text |Cite
|
Sign up to set email alerts
|

Listeriosis in Pregnant Women in Morocco: A Case Report

Abstract: Listeriosis is a rare infectious disease. Pregnant women with listeriosis represent 1/3 of all listeriosis cases. Listeriosis is a foodborne disease. Sporadic as well as epidemic cases of listeriosis are usually related to contaminated processed food, especially meat dishes served in fast-food restaurants and dairy products. Pregnant women are at an increased risk for listeriosis infection. Unfortunately the symptoms are not specific and the diagnosis presents a considerable challenge. Although the literature … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 8 publications
(9 reference statements)
0
5
0
Order By: Relevance
“…In the European Union, the incidence of listeriosis is about 0.47 cases per 100, 000 population [4] and 0.24 cases per 100, 000 population in the United States [13]. In Morocco, the actual incidence of listeriosis remains unknown due to the lack of epidemiological surveillance, in fact only one case of neonatal listeriosis has been reported [14]. However, several studies showed the prevalence of L. monocytogenes in raw and processing foods [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…In the European Union, the incidence of listeriosis is about 0.47 cases per 100, 000 population [4] and 0.24 cases per 100, 000 population in the United States [13]. In Morocco, the actual incidence of listeriosis remains unknown due to the lack of epidemiological surveillance, in fact only one case of neonatal listeriosis has been reported [14]. However, several studies showed the prevalence of L. monocytogenes in raw and processing foods [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Human listeriosis can manifest as septicemia, meningoencephalitis, abortion or neonatal infection with high case fatality rate (20e30%) even in the absence of resistance to reference antibiotic treatment (Charlier et al, 2017;Morvan et al, 2010). In Morocco, the incidence of human listeriosis remains unknown due to the absence of epidemiological surveillance (Cohen et al, 2006;Maertens de Noordhout et al, 2014), and so far only one case of a neonatal listeriosis has been reported (Benabdejlil et al, 2015;Benomar et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…In Algeria, Ramdani-Bouguessa and Rahal [144] report two listeriosis cases in newborns based on a single site (same hospital) investigation. In Morocco, there is a high public health vigilance to listeriosis in pregnant women; thus, for any case where a pregnant woman to be hospitalized with signs of a bacterial infection or unknown infection, L. monocytogenes infection should be suspected [145]. There is a need for strengthening surveillance systems of foodborne zoonoses in general, and for L. monocytogenes in particular, in the Arab countries.…”
Section: Listeria Spp and Listeria Monocytogenes In The Food Chain In The Arab Worldmentioning
confidence: 99%